Konsep Kafa’ah Dalam Pernikahan: (Studi Analisis Pemikiran Sayyid Qutb dalam Tafsir Fii Zilalil Qur’an) - Azizah, Hanifatu (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Marriage in Islam is considered a very important institution and is seen as a means of building a harmonious and happy family. One important aspect of Islamic marriage is the kafa'ah relationship, which refers to the compatibility or compatibility between husband and wife in various respects, including religion, ethnicity, socio-economic and personal characteristics. This research concludes that it is important to understand the concept of kafa'ah in marriage. The concept of kafa'ah is not a requirement for the validity of a marriage, but is only a suggestion which will lead us to a marriage that leads to sakinah mawaddah and warahmah. The aim of this research is to provide a deeper understanding of the concept of kafa'ah in marriage according to Sayyid Qutb, explore the relevance of modern Muslim society, understand the construction of the interpretation of Fii Zilalil Qur'an, and understand the process of forming kafa'ah. In writing this, it is hoped that this study will be able to provide insight to all readers regarding kafa'ah. As well as expanding the body of knowledge regarding kafa'ah quoted from the Koran. This type of research uses qualitative research and the research data comes from the library, while the primary source in this research is the interpretation of the Fii Zilalil Qur'an. The method used in the research is a qualitative approach while the type is library research. The data analysis method used in this research is descriptive analysis.